The Role of Vocational Education Policy in South Sulawesi by Providing Quality Labor for Local Industries - Muh. Khadapi (Generasi Sains Indonesia, 2024)
This study does a thorough statistical analysis to determine the impact of vocational education on job outcomes in South Sulawesi. Data was gathered from participants in vocational education programs and industries in the region, with an emphasis on variables such as industry relevance, entrepreneurial abilities, education level, job satisfaction, and demographics. Descriptive statistics suggested that participants, who were primarily diploma-educated, had positive evaluations of the quality of vocational education and industrial relevance. Paired-sample t-tests revealed significant increases in work satisfaction following vocational education training. Regression analysis revealed that sector relevance and entrepreneurial abilities are strong determinants of employment outcomes. The ANCOVA findings revealed differences in opinions of vocational education quality based on school type. Pearson correlational studies revealed significant positive relationships between industry relevance, entrepreneurial skills, educational level, and work satisfaction.